Brucellosis Prevalence in Livestock of Tavush and Kotayk Marzes of Armenia and Assessment of Diagnostic Algorithm - Danelyan, H. M.; Arner, R. J. (ՀԱԱՀ հիմնադրամ)
Brucellosis is a common bacterial zoonosis caused by Brucella spp., which are facultative intracellular gram-negative cocco-bacilli, causing disease in cattle, small ruminants, and humans. The occurrence of brucellosis is widespread across a wide geographical area as well as endemic throughout the Caucasus region. The Ministry of Agriculture of Armenia has adopted a diagnostic algorithm consisting of screening samples with the Rose Bengal Test (RBT) followed by confirmation with the complement fixation test (CFT). This study determined the feasibility of the algorithm and diagnostics in Armenia. Sampling and testing were conducted in two marzes of Armenia with disparate brucellosis prevalence. The screening was performed in 2020 at regional laboratories, followed by retesting at the reference laboratory with RBT and confirmation by CFT. Results indicated that RBT testing was reproducible between laboratories, although positive rates in CFT testing were slightly higher. Brucellosis incidence in cattle was not geographically dependent, while sheep incidence was affected by location. The addition of CFT to the diagnostic algorithm improves the results.
Keywords: Veterinary Science and Animal Breeding